Examining the urban regeneration of public cultural space using multi-scale geospatial data: a case study of the historic district in Jinan, China - Xu, Yabing; Tong, Hui; Chen, Meng; Rollo, John; Zhang, Ruijie (Frontiers in Built Environment, 2023)
Introduction: Historical-cultural landscapes and urbanscapes integrate regional culture, collective memory, urban patterns, living habits, and other related historical and spatial information, and are important places for expressing the values of urban space. This study analyzes cultural landscapes and urbanscapes from the perspective of spatial values, taking the Baihuazhou historic and cultural district in Jinan as an example to analyze the spatial identification of public cultural space. The significance of this research lies in examining the urban regeneration of public cultural space using multi-scale geospatial data from both an objective and subjective perspective. This methdology is based on a large body of previous literature in relation to cultural heritage, and draws on a comprehensive understanding of the field. Methods: This study applies spatial syntax, visual graph, and survey analyses, focusing on urban spatial patterns, spatial culture, and spatial memory as heritage values. Results: The analysis results reveal that historic districts generally do not have good accessibility, predominantly because of the disorganized texture of the buildings and absence of spatial consistency. Discussion: There should be improved dynamic spatial identification and accessibility in older urban environments and enhancement of local spatial identification memory by increasing sightline accessibility. Based on consideration of values, corresponding suggestions are made from the three perspectives of urban space, cultural landscapes, and local collective memories to provide a reference for the protection of the Baihuazhou historic district and promote the preservation and development of similar heritage spaces.